Boundary layer flow and heat transfer of carbon nanotube over moving plate and stretching/shrinking sheet with stability analysis - Anuar, Nur Syazana (2021)
This study has been undertaken to solve numerically the boundary layer flow and heat transfer over various geometric surfaces such as horizontal and vertical moving plate, stretching/shrinking sheet and stretching/shrinking cylinder of carbon nanotubes subjected to different effects (slip, suction, magnetohydrodynamic, chemical reaction). These problems took into account two types of carbon nanotubes, namely single–wall carbon nanotubes (SWCNT) and multi–wall carbon nanotubes (MWCNT) that were dispersed into base fluids (water and kerosene). The governing partial differential equations were transformed into a system of nonlinear ordinary differential equations using a similarity transformation which was then solved numerically using a bvp4c function in MATLAB software. Numerical results for the local skin friction and local Nusselt number, which represents the heat transfer rate at the surface as well as velocity, temperature and concentration profiles were presented graphically and discussed in detail. The results show that all of the problems possessed dual solutions for a certain range of parameter, hence a stability analysis was performed to verify the stability of the solutions. The local skin friction, the local Nusselt number and concentration are significantly influenced by all the parameters studied, such as the nanoparticle volume fraction, moving parameter, slip parameter, suction parameter, mixed convection parameter, stretching/shrinking parameter, homogeneous parameter, heterogeneous parameter, nonlinear parameter, magnetic parameter, curvature parameter, Schmidt number and chemical reaction parameter. It was noticed that the nanoparticle volume fraction can increase the heat transfer rate and accelerates the cooling process. Furthermore, the kerosene–SWCNT offers a higher heat transfer efficiency compared to other carbon nanotubes. From the stability analysis, it was found that the first solution is stable, while the second solution is unstable.